Components of a Quality Education: A literature review - Peter Mduwile; Dulumoni Goswami (Institute of Educational, Research, and Community Service, 2024)
Education is an essential human entitlement and a crucial catalyst for sustained progress. Quality education influences individuals, societies, and economies by imparting the knowledge, skills, and values needed for personal satisfaction and societal advancement. The concept of ‘Components of quality education' encompasses various elements essential for ensuring that all learners receive an education that is relevant, equitable, and effective. Some educationists contend, however, that determining what makes an education good requires an objective yardstick because education quality is a subjective matter involving multiple dimensions of reference. That being said, this paper looks at a few crucial markers that, if followed, would help solve the issue of low learning standards. A qualitative approach was used by reviewing different literature concerning the topic. The paper briefly addresses several components of providing high-quality education, including a standardized curriculum, excellent teachers, practical students, suitable resources, capable leaders, and understanding parents. As a result of this study, A Teaching Learning Support (TLS) model for quality education has been created.